Study of the functional domains of the PTGS suppressor V2 from geminivirus Beet curly top virus (BCTV) - Luna, Ana P.; Rodríguez-Negrete, Edgar; Morilla, Gabriel; Castillo-Garriga, Araceli; Rodríguez-Bejarano, Eduardo (My University, 2019)
Geminiviruses constitute a group of plant viruses that infect vegetable crops all over the world. Among the Geminiviridae family, the genera Mastrevirus, Begomovirus and Curtovirus are the most abundant. Suppression of gene silencing is a key mechanism for viral infection in plants. In begomovirus, V2 is a strong posttranscriptional gene silencing suppressor. We recently showed that V2 from curtovirus Beet curly top virus (BCTV) is a PTGS suppressor by impairing the RDR6/SGS3 pathway, as V2 from begomovirus. In order to identify the domains involved in the suppression activity and viral pathogenicity, we performed an alignment of several begomovirus and curtovirus V2 proteins. A protein kinase C (PKC) phosphorylation motif essential for suppression activity in begomovirus (P1) was found in all analysed sequences. We also found similar hydrophobic profiles, with two hydrophobic domains (H1 and H2) followed by a long hydrophilic domain. Then we generated BCTV V2 mutant proteins and performed transient assays in Nicotiana benthamiana plants to test their suppression activity. We also expressed them from a Potato virus X-derived vector to check the symptoms produced. Additionally, their subcellular localization was determined. Finally, we produced BCTV viruses mutated in the different domains and N. benthamiana plants were infected, analysing virus levels and symptoms produced. The results showed that P1, H1 and H2 are involved in the suppression activity and viral pathogenicity.
Keywords: Genética - Congresos; PTGS; Geminivirus